2020
DOI: 10.1089/jpm.2019.0100
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Use of Inpatient Palliative Care Consultation May Lead to Higher Readmissions and Costs in End-Stage Liver Disease

Abstract: Background/Aims: Patients with end-stage liver disease (ESLD) have a high risk for readmission. We studied the role of palliative care consultation (PCC) in ESLD-related readmissions with a focus on health care resource utilization in the United States. Methods: We performed a retrospective longitudinal analysis on patients surviving hospitalizations with ESLD from January 2010 to September 2014 utilizing the Nationwide Readmissions Database with a 90-day follow-up after discharge. We analyzed annual trends in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…On analyzing the national readmission database, we found that PC was associated with a significantly reduced odds of 30-d readmission in alcohol associated ESLD patients, with an adjusted odds ratio of 0.35 on multivariate analysis, accounting for several factors found to be associated with readmission rates such as age and ACLF score. We found that the rate of readmissions in our cohort of alcohol-associated ESLD patients with C use was lower than that of all ESLD patients which has been studied before[ 24 , 25 ]. Also, utilization of PC was lower than all-ESLD patients, where it was 5.3% vs 4.4% for our cohort of patients.…”
Section: Discussionmentioning
confidence: 69%
“…On analyzing the national readmission database, we found that PC was associated with a significantly reduced odds of 30-d readmission in alcohol associated ESLD patients, with an adjusted odds ratio of 0.35 on multivariate analysis, accounting for several factors found to be associated with readmission rates such as age and ACLF score. We found that the rate of readmissions in our cohort of alcohol-associated ESLD patients with C use was lower than that of all ESLD patients which has been studied before[ 24 , 25 ]. Also, utilization of PC was lower than all-ESLD patients, where it was 5.3% vs 4.4% for our cohort of patients.…”
Section: Discussionmentioning
confidence: 69%
“…The present study suggests that interventions that optimize care coordination and safe discharge plans may be an effective solution. In fact, several recent studies, including one randomized controlled trial, have highlighted the effect of specialty palliative care consultation in reducing readmissions for patients with cirrhosis, consistent with this concept (18)(19)(20). In the outpatient and community settings, only one intervention, incorporating multidisciplinary care management and same day hospitals for procedures in hepatology clinics, effectively reduced both readmissions and mortality in a cohort of patients with cirrhosis (21).…”
mentioning
confidence: 78%
“…Similarly, palliative care consult has been reported to be used in only 4.5% to 5.3% of hospitalisations with end-stage liver disease in the US. 28,29 Symptom burden is high among patients with end-stage liver disease and in those with HRS, resulting in poor quality of life. 15 Use of palliative care in patients without cancer has been shown to reduce hospitalisations, symptom burden, and cost of medical care, with an improved quality of life score.…”
Section: Discussionmentioning
confidence: 99%